2021
DOI: 10.1182/bloodadvances.2020003843
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion of target antigens to preimmunized recipients: a new mechanism in transfusion-related acute lung injury

Abstract: Transfusion-related lung injury (TRALI) is a serious side effect of blood transfusion. Exclusion of antibody carriers from the donor pool has significantly decreased the number of cases, but TRALI remains the leading cause of transfusion-related morbidity and mortality in industrialized countries. Here, we show that proteins released from donor cells during processing of blood components are capable of inducing a new type of reverse TRALI when transfused to preimmunized recipients. First, we show that soluble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…This suggests that the protein encoded by CD177 c.1291A still binds to PR3. It has been demonstrated that both proteins interact in their soluble form in vitro and it was speculated that CD177 may function as a protective agent that down-regulates the enzymatic activity of PR3 [ 7 , 13 ]. Although the conclusion of co-localisation of PR3 with CD177 c.1291A was based on a comparison of co-localisation of wildtype CD177 with PR3 (as a known fact), given the limitations of the fluorescence microscopy technique for inferring comparable co-localisation of CD177 c.1291 A with wild-type CD177, alternative techniques such as surface plasmon resonance analysis of PR3 as a ligand for immobilised CD177 c.1291A or wildtype are required to support this conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the protein encoded by CD177 c.1291A still binds to PR3. It has been demonstrated that both proteins interact in their soluble form in vitro and it was speculated that CD177 may function as a protective agent that down-regulates the enzymatic activity of PR3 [ 7 , 13 ]. Although the conclusion of co-localisation of PR3 with CD177 c.1291A was based on a comparison of co-localisation of wildtype CD177 with PR3 (as a known fact), given the limitations of the fluorescence microscopy technique for inferring comparable co-localisation of CD177 c.1291 A with wild-type CD177, alternative techniques such as surface plasmon resonance analysis of PR3 as a ligand for immobilised CD177 c.1291A or wildtype are required to support this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that transfused CD177/PR3 complexes present in blood components may become adsorbed to PECAM-1 on activated endothelial cells. Here, they can trigger endothelial barrier dysfunction and transfusion-related acute lung injury TRALI in anti-HNA-2 antibody carriers [ 13 ]. We are currently unable to state whether variant CD177/PR3 is also able to interact with PECAM-1, but data obtained in the study presented here have not brought evidence that would argue against it.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32][33][34] However, seronegative cases exist, "transfused ARDS" counts increase despite mitigation, and reverse TRALI is described. [35][36][37][38][39][40][41][42][43] TRALI may also have a "too-sick" or "not-sick-enough" underrecognition bias, with consideration dismissed despite heightened vulnerability in the already-critically ill on the one hand, and constraints upon serologic examinations on the other, be this due to less serious or convincing cases, costs, and/or hidden tensions on retaining high-value/performance donors. seronegative ones.…”
Section: The Challenge Of Accurate Crtr Diagnosis and The Inherent Co...mentioning
confidence: 99%
“…PECAM-1 on pre-activated endothelial cells absorbs soluble CD177/PR3 complex from plasma. Binding of CD177 isoantibodies to the absorbed CD177/PR3 complex on endothelial cells, induced endothelial barrier dysfunction implicated in the mechanism of anti-CD177 mediated reverse TRALI [74]. In severe cases of COVID-19 infections, progressive respiratory failure results from immunothrombosis that is driven by activated neutrophils and platelets.…”
Section: Nb Antigenmentioning
confidence: 99%